(untitled) (GEOgraphia, 2009)
O presente artigo aborda a questão dos recursos hídricos e a sustentabilidade do desenvolvimento para discussão de subsídios para melhoria do uso da água, - elemento essencial à vida. -, no âmbito de bacias e sub-bacias hidrográficas. Qualquer ação ou política desenvolvida para tratar dos recursos hídricos, só colherão bons resultados se considerarem as bacias de drenagem como unidades de planejamento e gestão ambiental. A título de exemplo, considerou-se o Plano de Recursos Hídricos do Estado do Ceará, concebendo-o como um estudo de caso da Sub-bacia Metropolitana do Pacoti - Ceará. Abstract The present work approaches the hydrological resources within the sustainable development realm, taking into account the uneven resource distribution in Semi-Arid regions such as the Northeastem Brazil and the Pacoti river basin in the State of Ceará. Although obvious, the water resources are essential to life. Based on this principie the idea of sustainable development is fully discussed on a local and global basis, so that to emphasize how low are the human and social development indexes related to local inhabitants. A poor State in a poor Region of a developing country, such as Brazil, shouldn’t operate without local political bias. Despite the local improvement translated into a more active participation of locals, some rural projects are producing better results to the rural people. Planning the years ahead seems to be the only way to provide a better life to future generation.